2006
DOI: 10.1111/j.1365-2133.2006.07179.x
|View full text |Cite
|
Sign up to set email alerts
|

The dermal stem cell factor and c-kit are overexpressed in melasma

Abstract: SummaryBackground The pathogenesis of melasma has not yet been clearly demonstrated. We tried to determine whether the stem cell factor (SCF) and its receptor c-kit are involved in the mechanism of hyperpigmentation of melasma because this factor is highly implicated in the stimulation of melanocyte function in vitro and in vivo. Objectives The present study was conducted to investigate the expression of SCF and c-kit on the lesions of melasma compared with nonlesional skin. Patients/methods Skin samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(145 citation statements)
references
References 14 publications
6
135
0
4
Order By: Relevance
“…Também é conhecida a regulação por oncogene-a relacionado ao crescimento, para interações entre melanócitos e ceratinócitos, fator de crescimento hepatocítico e fator stem cell,l tipo solúvel, para interações entre fibroblastos e melanócitos. 1,79,80 Esta inter-relação também envolve alguns receptores específicos expressos nos melanócitos, como: o receptor de endotelina B, o receptor de fator stem cell e c-KIT. A up ou downregulation, dessa rede interligada, está intrinsecamente envolvida na estimulação das funções melanocíticas, em várias desordens epidérmicas que cursam com alterações na pigmentação.…”
Section: Melasmaunclassified
See 2 more Smart Citations
“…Também é conhecida a regulação por oncogene-a relacionado ao crescimento, para interações entre melanócitos e ceratinócitos, fator de crescimento hepatocítico e fator stem cell,l tipo solúvel, para interações entre fibroblastos e melanócitos. 1,79,80 Esta inter-relação também envolve alguns receptores específicos expressos nos melanócitos, como: o receptor de endotelina B, o receptor de fator stem cell e c-KIT. A up ou downregulation, dessa rede interligada, está intrinsecamente envolvida na estimulação das funções melanocíticas, em várias desordens epidérmicas que cursam com alterações na pigmentação.…”
Section: Melasmaunclassified
“…A up ou downregulation, dessa rede interligada, está intrinsecamente envolvida na estimulação das funções melanocíticas, em várias desordens epidérmicas que cursam com alterações na pigmentação. 79,80 Achados imunohistoquímicos sugerem que uma forte imunorreatividade de α-MSH na pele lesada de melasma é um dos maiores fatores na gênese dessa doença. A relação entre área fotoexposta e a maior imunorreatividade de α-MSH na pele lesada ainda não foi elucidada.…”
Section: Melasmaunclassified
See 1 more Smart Citation
“…Very recently, we suggested that dermal inflammation induced by accumulation of UV irradiation may be associated with activation of fibroblasts, which result in the up-regulation of stem cell factor in melasma dermal skin leading to increased melanogenesis [3]. These studies have given us new insights on the pathogenesis of melasma, in particular, that the dermal environment may have an important role in the development of melasma.…”
mentioning
confidence: 97%
“…Stressful stimuli, such as UV rays and inflammation, can cause melanocytes to become easily influenced by Stem Cell Factor (SCF), a cytokine, and Melanocyte-Stimulating Hormone (MSH), the hormone that promotes melanin synthesis. Melanocytes are activated by receiving these factors through various signal transduction systems that take place within the melanocytes [7,8]. It has been reported that there are individual differences in susceptibility to the appearance of lentigines on the skin, and Melanocortin Receptor Subtype 1 (MC1R) varies in people with melasma and freckles.…”
Section: Introductionmentioning
confidence: 99%